High permittivity, breakdown strength, and energy storage density of polythiophene-encapsulated BaTiO3 nanoparticles - Khan, Adnanullah; Habib, Amir; Afzal, Adeel (Beilstein Journal of Nanotechnology, 2020)
High permittivity and breakdown strength are desired to improve the energy storage density of dielectric materials based on reinforced polymer composites. This article presents the synthesis of polythiophene-encapsulated BaTiO3 (BTO-PTh) nanoparticles via an in situ Cu(II)-catalyzed chemical oxidative polymerization of thiophene monomer on hydrothermally obtained tetragonal BTO nanocrystals. The formed core–shell-type BTO-PTh nanoparticles exhibit excellent dielectric properties with high permittivity (25.2) and low loss (0.04) at high frequency (106 Hz). A thick PTh encapsulation layer on the surface of the BTO nanoparticles improves their breakdown strength from 47 to 144 kV/mm and the energy storage density from 0.32 to 2.48 J/cm3. A 7.75-fold increase in the energy storage density of the BTO-PTh nanoparticles is attributed to simultaneously high permittivity and breakdown strength, which are excellent for potential energy storage applications.
Keywords: barium titanate (BaTiO3) nanoparticles; breakdown strength; dielectric materials; energy storage; polythiophene